Menilik Dominasi Bahasa Mitos Dalam Sosiokultural Sasak - Zainul muttaqin; Mu’awanah Mu’awanah (Fakultas Tarbiyah Institut Agama Islam Hamzanwadi NW Pancor, 2020)
The purpose of this study is to describe the process of hegemony in the language of Tithe Ringkok Ratu myth in North Masbagik Village. The problem formulation of this research is